Perspective on intestinal microbiota temporal changes of herbal additives treated shrimp in a natural aquaculture setting - Lin, Xu-Yin; Shih, Yi-Jia; Zhang, Xian-Jing; Cai, You-Shu; Zhou, Xiao-Wen; Chen, Jung-Sheng (Frontiers in Marine Science, 2024)
Shrimp is an important aquaculture species worldwide. The use of antibiotics to suppress disease outbreaks has led to antibiotic resistance; however, probiotics or natural herbal additives can enhance the health of farmed shrimp. In this study, the effects of formulations containing natural herbs and probiotics on shrimp farming were explored. Following indoor shrimp farming, the shrimp were returned to outdoor natural ponds for 1 week in the presence of a fermented probiotic product. The gut microbiota was surveyed using 16S rRNA gene sequencing at 1, 2, 3, and 8 weeks after the natural pond release. The results showed that Vibrio-related bacterial genera increased significantly in the shrimp intestinal microbiota at 2 weeks and were particularly high at 3 weeks after natural pond release. The phyla Firmicutes, Bacteroidetes, Vibrio-related bacteria, and the genus Cetobacterium emerged as crucial bacteria linked to shrimp health and growth. Overall, the diversity of the shrimp intestinal microbiota was lower upon release into the natural pond. However, this outcome may be associated with dysbiosis or influenced by the natural environment. Further research is warranted to substantiate these findings. A perspective on the shrimp gut microbiota provides important information for aquaculture management and explains the implementation of control measures.